Spite and Development - Fehr, Ernst; Hoff, Karla; Kshetramade, Mayuresh (World Bank, Washington, DC, 2012)
In a wide variety of settings, spiteful preferences would constitute an obstacle to cooperation, trade, and thus economic development. This paper shows that spiteful preferences - the desire to reduce another's material payoff for the mere purpose of increasing one's relative payoff - are surprisingly widespread in experiments conducted in one of the least developed regions in India (Uttar Pradesh). In a one-shot trust game, the authors find that a large majority of subjects punish cooperative behavior although such punishment clearly increases inequality and decreases the payoffs of both subjects. In experiments to study coordination and to measure social preferences, the findings reveal empirical patterns suggesting that the willingness to reduce another's material payoff - either for the sake of achieving more equality or for the sake of being ahead - is stronger among individuals belonging to high castes than among those belonging to low castes. Because extreme social hierarchies are typically accompanied by a culture that stresses status-seeking, it is plausible that the observed social preference patterns are at least partly shaped by this culture. Thus, an exciting question for future research is the extent to which different institutions and cultures produce preferences that are conducive or detrimental to economic development.